Students’ perception towards the usage of the big book / Dr. Normaliza Abd Rahim and Nik Ismail Harun - Abd Rahim, Normaliza; Harun, Nik Ismail (Universiti Teknologi MARA Cawangan Pahang, 2010)
Reading stories to children would be a challenging and utmost important activity to enhance learning and understanding a language. Various techniques or activities have been proposed in the literature to make reading an enjoyable activity in the classroom. Amongst the many, reading a big book is one of the activities recommended to facilitate students’ comprehension of a story delivered by the teacher. This paper focuses on the use of the big book in story reading sessions in two classrooms of primary schools in a rural area in Malaysia. The objectives were to assess students’ understanding of the content of or the graphics used in the big book and to examine their comments and opinion on the contents of the big book and its use. One hundred subjects aged seven years old from two literacy classrooms in a rural area school participated in the study. Five other subjects, selected at random, participated in the interview session. Findings of the study revealed that the use of the big book seemed to be of an advantage as it creates fun and meaningful learning of English in the classroom, as well as making reading activity an enjoyable one.